Purification and cytotoxicity assay of tomato (Lycopersicon Esculentum) leaves methanol extract as potential anti-cancer agent - Wan Chik, Wan Dalila; Amid, Azura; Jamal, Parveen (2010)
This research studied the cytotoxicity effect of tomato leaves methanol extract on cancer cells to address potential therapeutic in MCF-7 breast cancer cell lines and its toxicity towards Vero cells. The extraction was done in a shake flask by 82% methanol, 1:10 (w/v), agitated at 22 °C with 110 rpm within 24 hours. Later, purification process was started by thin layer chromatography (TLC) subjected to determine the best mobile phase for compound separation and collection by means of column chromatography. Next, the effect of purified sample towards MCF-7 breast cancer cell lines and Vero cells were observed using in vitro cytotoxicity assay to indicate its active fractions and its half maximal inhibitory concentration (IC50). Purified sample gave a rational effect towards MCF-7 breast cancer cells with IC50 value of 5.85 μg/ml compared to Taxol with IC50 value of 0.039 μg/ml. The purified sample can also be judged to be harmless as it has IC50 value of 765.6 μg/ml in Vero cells treatment while Taxol gave IC50 value of 0.045 μg/ ml.